COMPARATIVE EVALUATION ON THE POTENTIALS OF SHEEP RUMEN CONTENTS FOR BIOGAS GENERATION (FUDMA JOURNAL OF SCIENCES, 2022)
Biogas refers to a gas produced by the biological breakdown of organic matter in the absence of oxygen. It is as a clean biofuel produced by microorganism during anaerobic digestion of organic matter. The study was carried out to determine the potentials of sheep rumen contents for biogas production through anaerobic digestion. Proximate analysis was carried out on the substrate. The results shows that nitrogen, potassium and phosphorus have 0.58 ± 0.02 (mg/ml), 425 ± 5.00 (mg/ml), and 2.57 ± 0.03 (mg/ml) respectively. After proximate analysis, four (4) local digesters with capacity of 500g tins were designed and used for the collection of gas via passage pipe systems. The digesters were used to digest the slurry (mixture of Sheep rumen content and water) which were mixed in the ratio of 2:1 for a period of eight weeks (56 days) retention time until the biogas reduced significantly. The pH values of the slurries were adjusted to neutral. The digesters were stirred thrice daily to avoid scum formation in the digesters and allow for easy escape of gas produced. The total average yield of the gas produced were 820 cm3, 1070 cm3, 780 cm3, and 660 cm3 for D1, D2, D3, and D4 respectively. Isolation of Microorganisms were caried during the production where B. subtilis, E. coli, P. aeruginosa, and S. aureus were found.  Biogas production from organic wastes which is an eco-friendly, which helps to solve most countries energy crisis.
Keywords: Biogas; Biofertilizer; Sheep Rumen Contents; Digester; Anaerobic Digestion; Slurry